2013
DOI: 10.1370/afm.1584
|View full text |Cite
|
Sign up to set email alerts
|

What Do You Expect From a Doctor? Six Habits for Healthier Patient Encounters

Abstract: Expectations lie at the heart of America's health care crisis. Although doctors cannot control for the unrealistic demands of a consumer-centric society, we might ask what we would want in a physician. Someone who listens longer and lets us express ourselves in our own words? Someone who cares about the outcome-our personal outcome-and not just the "clinical course"? Most patients do not demand perfection. Not cure. Not even relief, no matter what the TV commercials promise or how badly they wish them to be tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…For healthcare staff, however, consultation with patients is routine work, and has no significant impact on their perception of PPR. Unlike consultation, listening focuses on patients, and also considers their psychological and social needs [ 14 , 15 , 53 ]. Recent increases in the incidence of chronic non-communicable diseases mean that patients’ need to be listened to is greater than ever [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…For healthcare staff, however, consultation with patients is routine work, and has no significant impact on their perception of PPR. Unlike consultation, listening focuses on patients, and also considers their psychological and social needs [ 14 , 15 , 53 ]. Recent increases in the incidence of chronic non-communicable diseases mean that patients’ need to be listened to is greater than ever [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can be explained by the fact that, to some extent, patients in Shandong, Chongqing, Shanxi preferred village clinics, township health centers, county hospitals, irrespectively. It was reported that patients' habit of visiting doctors had some associations with the combination of geographic factor, with the ability of health care delivery for different level of medical institutions, with the economic situation and the payment methods [19][20][21][22]. In this study, we found that the ability of health care delivery for village clinics in Shandong was higher than those in other provinces.…”
Section: Who Is Eligible To Take Over Gatekeeping?mentioning
confidence: 54%
“…Not even relief. What we all desire is a plan that connects us to another human beingour doctor-which is a kind of relief all its own [1]. Patient-centered medical care and context (family and community), which is the own of general medicine, despite technology is still a profession that refers to a patient, a pair of ears, a pair of eyes and a pair of hands [8].…”
Section: /6mentioning
confidence: 99%
“…Neither patient nor doctor should expect the doctor to be a parent, or brother. Yet bedside manner, face-to-face time, and a sense of connection-the doctor-patient relationship-matter as much as the services that are delivered [1].…”
Section: Ulysses Syndromementioning
confidence: 99%